2022
DOI: 10.3727/152599521x16367300695870
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Congestion During Running Events from The Perspective of Runners: Prevalence, Impact on Safety And Satisfaction, and Preferred Controls

Abstract: This study aimed to examine the views of runners regarding their experiences with congestion during running events, including its prevalence, its impact on their safety and satisfaction, and their preferred controls to mitigate congestion. Runners (n = 222) with varied experience participating in running events (1-5+ years, 5-km races to Ultramarathons, and a mixture of road, trail, and cross-country events) completed an electronic survey. The survey was developed to assess the characteristics of respondents, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…In this regard, survey data provided from 35 race directors with experience coordinating large running events in Australia indicated that almost half of the respondents (43%) had received feedback from runners related to congestion during their events, with this feedback mostly related to the impacts of congestion on runner satisfaction (94%) and safety (62%) [4]. Likewise, survey data from 222 runners who have participated in running events indicated most of them had experienced congestion when waiting for race commencement (93%), as the race commenced (97%), and on-course during the race (88%), with their experiences encountering congestion "somewhat" to "extremely" impacting (i.e., rating of at least 3 on a 5-point Likert item) their satisfaction (73%) and safety (43%) during the event [5]. In turn, many of the surveyed runners indicated they had tripped or slipped at the beginning of a race (38%), fell while running (27%), or required medical treatment (9%) due to congestion at running events [5], emphasizing participant congestion can lead to incidents and injuries of a concerning nature to race directors and runners alike.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this regard, survey data provided from 35 race directors with experience coordinating large running events in Australia indicated that almost half of the respondents (43%) had received feedback from runners related to congestion during their events, with this feedback mostly related to the impacts of congestion on runner satisfaction (94%) and safety (62%) [4]. Likewise, survey data from 222 runners who have participated in running events indicated most of them had experienced congestion when waiting for race commencement (93%), as the race commenced (97%), and on-course during the race (88%), with their experiences encountering congestion "somewhat" to "extremely" impacting (i.e., rating of at least 3 on a 5-point Likert item) their satisfaction (73%) and safety (43%) during the event [5]. In turn, many of the surveyed runners indicated they had tripped or slipped at the beginning of a race (38%), fell while running (27%), or required medical treatment (9%) due to congestion at running events [5], emphasizing participant congestion can lead to incidents and injuries of a concerning nature to race directors and runners alike.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, survey data from 222 runners who have participated in running events indicated most of them had experienced congestion when waiting for race commencement (93%), as the race commenced (97%), and on-course during the race (88%), with their experiences encountering congestion "somewhat" to "extremely" impacting (i.e., rating of at least 3 on a 5-point Likert item) their satisfaction (73%) and safety (43%) during the event [5]. In turn, many of the surveyed runners indicated they had tripped or slipped at the beginning of a race (38%), fell while running (27%), or required medical treatment (9%) due to congestion at running events [5], emphasizing participant congestion can lead to incidents and injuries of a concerning nature to race directors and runners alike. Furthermore, reduced participant satisfaction with a running event may negatively impact the reputation of the event among prospective consumers, which can jeopardize the financial viability of the event [5].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations